2018
DOI: 10.26911/thejmch.2018.03.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors Associated with Anxiety and Delivery Pain

Abstract: Background: Anxiety and pain are physiologic symptoms experienced by mothers during birth delivery. However, if these symptoms are not well-managed they can cause low birth weight, prematurity, prolonged labor, and postpartum depression. This study aimed to analyze the psychosocial factors associated with anxiety and delivery pain. Subjects and Method: This was an analytical observational study with cross sectional design. The study was conducted at Gajahan community health center, Surakarta Hospital, and Muha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Labor pain is a physiological aspect for mothers in labor, but most women consider pain during labor to be the most intense pain that every woman feels 15 . Although pain during labor is not a pathological process, normal labor is still imagined as a very painful process 16 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Labor pain is a physiological aspect for mothers in labor, but most women consider pain during labor to be the most intense pain that every woman feels 15 . Although pain during labor is not a pathological process, normal labor is still imagined as a very painful process 16 .…”
Section: Discussionmentioning
confidence: 99%
“…According to a research Geisser M, Robinson M, Miller Q, found that 90% of women experienced pain associated with 37% moderate pain. Maternal pain in labor has many factors, ranging from family support, age, parity and perceptions of labor pain that have a significant effect on the pain felt 16,22 . Reading the Qur'an can reduce stress hormones, activate natural endorphins, increase feelings of relaxation, and divert attention from fear, anxiety and tension, improve the body's chemical system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the anxiety effects is the lack of exclusive breastfeeding (Field, 2017). There is a positive direct relationship between anxiety and labor pain (Nisa et al, 2018). Alladin (2016) states that any comprehensive therapy must include both conscious and unconscious therapies such as behavioral therapy, cognitive therapy, psychodynamic psychotherapy, therapy mindfulness and others in the treatment of anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%